2020
DOI: 10.3389/fmicb.2019.03126
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis and Caspase-2-Mediated Apoptosis of Astrocytes and Neurons, but Not Microglia, of Rat Hippocampus and Parenchyma Caused by Angiostrongylus cantonensis Infection

Abstract: Zhou et al. Lv's Manuscript in Frontiers in Microbiology obvious, suggesting that apoptosis and necroptosis but not autophagy or pyroptosis occurred in the brains of infected animals at 21 and 28 dpi. The results of RT-qPCR, western blot analysis, IF, flow cytometry and TEM further illustrated that necroptosis and caspase-2-mediated apoptosis occurred in astrocytes and neurons but not in microglia in the parenchyma and hippocampus of infected animals. This study provides the first evidence that neuronal and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 94 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, the interaction between RIP1 and FADD/Caspase-8 was notably enhanced after AC infection. In addition, we performed immunofluorescence to identify astrocytes undergoing apoptosis and this was similar to the outcome of astrocytes in rats infected with AC (Zhou et al 2019 ). For TNF-α-induced necroptosis, previous studies indicated that the downstream signalling axis was the RIP1/RIP3/MLKL pathway characterized by the formation of the RIP1/RIP3/MLKL complex (Wang et al 2019 ; Zhang et al 2018 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the interaction between RIP1 and FADD/Caspase-8 was notably enhanced after AC infection. In addition, we performed immunofluorescence to identify astrocytes undergoing apoptosis and this was similar to the outcome of astrocytes in rats infected with AC (Zhou et al 2019 ). For TNF-α-induced necroptosis, previous studies indicated that the downstream signalling axis was the RIP1/RIP3/MLKL pathway characterized by the formation of the RIP1/RIP3/MLKL complex (Wang et al 2019 ; Zhang et al 2018 ).…”
Section: Discussionmentioning
confidence: 91%
“…AC infection remains the main causative agent of eosinophilic meningitis worldwide (Flerlage et al 2017 ). As non-permissive hosts of AC (Ji et al 2017 ; Zhou et al 2019 ), mice and human beings could be infected by eating raw or uncooked snails containing third-stage larvae, which causes severe eosinophilic meningitis or encephalitis (Mengying et al 2017 ). Patients infected by AC suffered from a drastic inflammatory response in the host, neurological impairment and neurodegenerative lesions (Yan et al 2018 ; Yoshida et al 1996 ), finally leading to memory and cognitive deterioration as a result of the impaired function and irreversible cell death of brain cells (Mengying et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the cells were fixed in 2.5% glutaraldehyde (GA, Sigma-Aldrich, St. Louis, MO, USA) at 4 °C overnight and dehydrated in ethanol. The samples were captured using a TEM as described previously [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Escamilla et al [ 34 ] confirmed that Fasciola hepatica induced apoptosis in the peritoneal leucocytes of sheep in vivo. Zhou et al [ 35 ] provided the first evidence that neuronal and astrocytic necroptosis and caspase-2-mediated apoptosis are induced by Angiostrongylus cantonensis infection in the parenchymal. In this study, we confirmed that rBsCPI-1 significantly induces cell apoptosis through FCM.…”
Section: Discussionmentioning
confidence: 99%